Exploring the Effectiveness of Self-Healing Butterfly Technique for Anxiety Management: A Systematic Review - Tata Mahyuvi; Sukma Cahya Ramadhan (Yayasan Literasi Sains Indonesia, 2025)
The study aims to analyze the effects of butterfly hug therapy on anxiety levels through a systematic review of relevant studies. Journal searches were conducted using Semantic Scholar and Google Scholar, focusing on articles published between 2020 and 2024 in English and Indonesian. Inclusion criteria required full-text accessibility in PDF format, with keywords combining